PENGARUH FRAKSI ETIL ASETAT DAUN PILADANG (Solenostemon scutellarioides (L) Codd) TERHADAP KADAR KOLESTEROL TOTAL TIKUS PUTIH JANTAN - Verawati verawati; Mimi Aria; Iyun Julia Ningsih (LLDIKTI Wilayah X, 2017)
Hypercholesterolemia is a risk factor for atherosclerosis and vascular diseases. Medicinal plants with different content of secondary metabolites such as polyphenols and flavonoids are natural sources to cope hypercholesterolemia. This study aimed to determine the effect of ethyl acetate fraction of piladang leaves (Solenostemon scutellarioides (L) Codd) on serum cholesterol levels in hypercholesterolemic male rats. Rats were divided into 6 groups, each consisting of 6 animals: group I (negative control), group II (positive control), group III, IV and V were each given fraction of ethyl acetate doses respectively 100, 250 and 500 mg/kg and group VI (simvastatin as a comparator). Measurement of serum cholesterol levels were conducted with CHOD-PAP method using a photometer 5010. Result showed ethyl acetate fraction affects cholesterol levels of experimental animals with a lower value than the positive control. According to statistics of one way ANOVA followed by the Duncan test method SPSS 17 showed no significant differences (p> 0.05) on cholesterol levels in all given doses of ethyl acetate fraction. Group III(a dose of 100 mg / kg) was probably the most effective in lowering the blood cholesterol levels of experimental animals.